Evaluation of compositional micro-homogeneity in MOX fuels using lab based μ-XRF spectrometry. Issue 6 (16th May 2022) - Sanyal, Kaushik; Kanrar, Buddhadev; Dhara, Sangita; Pai, Rajesh V.
Abstract : Direct non-destructive evaluation of micro-homogeneity and agglomerate sizes (red zones) in nuclear fuel pellets prepared via different fabrication routes using μ-XRF. Abstract : A highly sensitive and simple micro-X-Ray Fluorescence (μ-XRF) based methodology has been developed for the direct non-destructive compositional analysis and micro-homogeneity studies of mixed oxide (MOX) fuel pellets of uranium and thorium prepared via different fabrication routes, using a micro-focused X-ray beam having a spot size of 35 μm × 50 μm on the sample surface. The developed methodology can be used to accurately determine the percentage of uranium present at each spot of the pellet sample. Based on this information a highly accurate and precise elemental mapping of uranium can be obtained in the nuclear fuel pellets having uranium in the concentration range from 2 to 50% with respect to thorium. Determination of elemental distribution within the pellets is very important to identify the uranium-rich agglomerates/hotspots present in fuel pellets. The developed method can also be used to determine the size of these agglomerates. Such information is necessary to assess the quality of the fuel pellets before their application in nuclear reactors. The above studies have shown that μ-XRF has potential for the routine non-destructive elemental analysis of MOX fuel samples. The laboratory based compact table-top μ-XRF instrument can be easily installed inside a glovebox and hence, the developed methodology can be extended to the compositional analysis of Pu based fuel pellets.